Association between major discrimination and deficit accumulation in African American cancer survivors: The Detroit Research on Cancer Survivors Study. Issue 10 (20th March 2023) - Mandelblatt, Jeanne S.; Ruterbusch, Julie J.; Thompson, Hayley S.; Zhou, Xingtao; Bethea, Traci N.; Adams‐Campbell, Lucile; Purrington, Kristen; Schwartz, Ann G.
Abstract: Background: Discrimination can adversely affect health and accelerate aging, but little is known about these relationships in cancer survivors. This study examines associations of discrimination and aging among self‐identified African American survivors. Methods: A population‐based sample of 2232 survivors 20–79 years old at diagnosis were enrolled within 5 years of breast ( n  = 787), colorectal ( n  = 227), lung ( n  = 223), or prostate ( n  = 995) cancer between 2017 and 2022. Surveys were completed post‐active therapy. A deficit accumulation index measured aging‐related disease and function (score range, 0–1, where <0.20 is robust, 0.20 to <0.35 is pre‐frail, and 0.35+ is frail; 0.06 is a large clinically meaningful difference). The discrimination scale assessed ever experiencing major discrimination and seven types of events (score, 0–7). Linear regression tested the association of discrimination and deficit accumulation, controlling for age, time from diagnosis, cancer type, stage and therapy, and sociodemographic variables. Results: Survivors were an average of 62 years old (SD, 9.6), 63.2% reported ever experiencing major discrimination, with an average of 2.4 (SD, 1.7) types of discrimination events. Only 24.4% had deficit accumulation scores considered robust (mean score, 0.30 [SD, 0.13]). Among those who reported ever experiencing major discrimination, survivors with four to seven types of discrimination events (vs. 0–1) had a large, clinically meaningful increase in adjusted deficits (0.062, p  < .001) and this pattern was consistent across cancer types. Conclusion: African American cancer survivors have high deficit accumulated index scores, and experiences of major discrimination were positively associated with these deficits. Future studies are needed to understand the intersectionality between aging, discrimination, and cancer survivorship among diverse populations. Abstract : African American cancer survivors have high deficit accumulated index scores, and experiences of major discrimination were positively associated with these deficits. Future studies are needed to understand the intersectionality between aging, discrimination, and cancer survivorship among diverse populations.